Impact of polymeric additives on the functionality of microfibrillar cellulose - Agarwal, Deepa (2016)
The aim of the work presented in this thesis was to investigate the impact of different mechanical treatments on the structure and physical properties of microfibrillar cellulose (MFC) and examine further changes upon drying of these MFC suspensions. It has been demonstrated that depending on the type of homogeniser and number of passes through the homogeniser results in a different variety of MFC with a distinct degree of fibrillation. An entangled network structure of MFC plays an important role in maintaining the rheological properties as well as water mobility in the system. Spin-spin relaxation time (T2) of the highly entangled microfibrils network indicates that the water mobility was higher in suspensions with a high degree of fibrillation, as compared to the low degree of fibrillation. It is now well established that during the drying stage MFC fibril-aggregates are formed due to strong intermolecular hydrogen bonds within the network structure. Due to a lack of redispersibility in water and the presence of fibril-aggregates, a non-homogenous distribution throughout the system was observed and the aqueous suspension of redispersed MFC shows a noticeable reduction in complex and shear viscosities. Hence, the next stage of the study focused on to stabilise the fibril-networks of microfibrils upon the drying, where the impact of different polymeric additives i.e. carboxyl methylcellulose (CMC), locust bean gum (LBG) and a blend of CMC/LBG was investigated. The addition of polymeric additives significantly improves the redispersibility of dried MFC in water with reduced fibrils aggregates. The interaction between microfibrils and additives are driven by surface OH-group-mediated hydrogen bonds; however the extents of these interactions are highly dependent on the type of additive used to stabilise the microfibrils. The point of the addition of polymeric additives plays an important role in terms of interaction between the polymeric additive and MFC. Co-processing of MFC and polymeric additives has a noticeable impact on the degree of fibrillation (visualised through light microscopy and degree of transparency) of the final MFC product. The presence of a charged polymeric additive such as carboxyl methyl cellulose (CMC) results in strong synergistic interaction with MFC, whereas weak synergistic interaction is reported with Locust bean gum (LBG). The addition of a CMC/LBG blend also showed strong synergistic interaction with MFC when added in a small amount. The amounts of additive present in the system have a noticeable impact on the viscoelastic properties of the suspensions. At ambient temperature, the MFC/additives suspensions formed a weak gel-like network. It was found that a polymeric additive forms a surface coating on MFC fibrils which protects the fibrils, to form strong intermolecular hydrogen bonds during the drying process, resulting in improved redispersibility of the dry product in an aqueous medium. The interaction between MFC and polymeric additives leads to an increase in moisture uptake even after drying process. Increase in water accessibility within the microfibril network was evident with Dynamic Vapour sorption analysis and low-temperature thermal transitions measured by Differential Scanning Calorimetry. This research also features a preliminary study on the potential application of MFC produced from softwood spruce as a dietary fibre for food application. This includes a comparison between the microstructure and different physical properties of softwood MFC (flakes and powder) with food grade commercial dietary fibres e.g. citrus fibres. Softwood MFC (both flakes and powder form) showed similar rheological properties to other cellulosic dietary fibres such as citrus fibres. Due to a highly entangled network structure softwood MFC showed the highest water retention values (also known as water holding capacity) as compared to other cellulosic fibres. A comparison of the rate of taste i.e. salt perception was also carried out, and the structural features of MFC affect this and appear to be more similar to soluble hydrocolloid solutions than the particulate systems such as citrus fibres. In summary, this thesis describes the mechanistic understanding of the interaction between MFC and different polymeric additives such as CMC and LBG. This research highlights the these interactions results in different microstructures affecting the functional properties of MFC such as redispersing behaviour, water mobility, low-temperature polymer-water interactions and rheological properties. Microfibrillar cellulose (MFC) are not only fundamentally interesting but most importantly they are practical, and certainly offers a more environmentally friendly, and cost-effective ingredient for various traditional commercial applications such as paints, composites and adhesives. This work also proves, for the first time, that the MFC from softwood can also be used as an ingredient for food applications as a bulking agent, stabilising agent, texture and viscosity enhancer.